Marxist-Leninist Conception of Ideology - Oizermanas, Teodoras (Problemos, 1976)
K. Marx and F. Engels were the first to apply the materialist principle of reflection, earlier applied only to epistemology, to social theory. Thus it became clear that the epistemological criteria were not sufficient for determining the real historical importance of social ideas. Therefore, sociological principles of their evaluation were formulated. On the basis of this discovery, the materialistic conception of history was formed which demands to substitute the distorted reflection of social life by an adequate one. V. I. Lenin, continuing the work of the founders of Marxism, substantiated the concept of the scientific ideology which presumes the existence of the social class the interests of which are in agreement with the objective trend of historical process. Marxism-Leninism means a unity of science and scientific ideology.